The Deductibility of the Aristotelian Modal Syllogism ◇E◻I◇O-1 from the Perspective of Knowledge Reasoning - Qiu, Jun (Transactions on Engineering and Computing Sciences, 2024)
Syllogistic reasoning has a significant impact on human society and human thinking. This paper firstly proves the validity of ◇E◻I◇O-1, which has great significance to ensure the soundness of all subsequent proofs, then there is other 41 valid Aristotelian modal syllogisms derived from ◇E◻I◇O-1 with the help of relevant rules, facts, and definitions. There are reducible relations between different Aristotelian modal syllogisms, so it has been given that consistent results for them. This paper studies their formalization and deductibility from the perspective of knowledge reasoning, and contributes to providing theoretical support for natural language information processing in computer science area.